Value of yoghurt - Yarosh, Y.; Strizhnova, Marianna (My University, 2014)
Dairy products are usually high energy-yielding food products. A production plant for the processing of milk is called a dairy or a dairy factory. Apart from breastfed infants, the human consumption of dairy products is sourced primarily from the milk of cows, yet goats, sheep, yaks, horses, camels, and other mammals are other sources of dairy products consumed by humans.
Keywords: біфідобактерії; лактобацилли; молочні продукти; казеїн; бифидобактерии; йогурт; лактобациллы; молочные продукты; казеин; bifidobacteria; lactobacilli; yogurt; dairy products; casein; кафедра іноземних мов професійного спрямування